2021
DOI: 10.1128/aem.02275-20
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Diversity within Common Protozoan Parasites as Revealed by a Novel Genomotyping Scheme

Abstract: Giardia duodenalis (syn. G. lamblia, G. intestinalis) is the causative agent of giardiasis, one of the most common diarrheal infections in humans. Evolutionary relationships among G. duodenalis genotypes (or subtypes) of assemblage B, one of two genetic assemblages causing the majority of human infections, remain unclear due to poor phylogenetic resolution of current typing methods. Here, we devised a methodology to identify new markers for a streamlined multi-locus sequence typing (MLST) scheme based on compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Finally, the typing scheme used in the present study may lack enough phylogenetic resolution to correctly differentiate between sub-assemblage BIII and BIV sequences. This issue has been highlighted in recent molecular studies for assemblage B and assemblage A sequences [46,47]. This important point emphasises the need of identifying new markers and of developing novel methods for MLST purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the typing scheme used in the present study may lack enough phylogenetic resolution to correctly differentiate between sub-assemblage BIII and BIV sequences. This issue has been highlighted in recent molecular studies for assemblage B and assemblage A sequences [46,47]. This important point emphasises the need of identifying new markers and of developing novel methods for MLST purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 81 Giardia-positive calf samples from the four districts, 31 were selected for molecular characterisation, of which 18 provided good sequence results; 14 were Assemblage E, three were Assemblage A, and one was Assemblage B. Subtyping the Assemblage A isolates revealed that two were AI and one could not be subtyped. Subtyping of the Assemblage B using multilocus sequence typing showed a close relationship with Algerian samples (37). Out of 11 Giardia-positive calf samples from urban farms, molecular characterisation was successful for six and all were Assemblage E.…”
Section: Molecular Characterisation Of Cryptosporidium and Giardia Fr...mentioning
confidence: 93%
“…The subtyping in this study was carried out at only the gdh locus. This presents a potential limitation since other studies have shown that sequencing typing at different loci can result in the assignation of multiple subtypes [ 2 , 35 ] and is why more studies are utilising multilocus sequence typing (MLST) [ 36 ]. However, this study sought to compared data from NGS to samples that had previously been characterised by Sanger sequencing at the gdh locus.…”
Section: Discussionmentioning
confidence: 99%